Materyalist teoloji ve presokratik felsefe: Alain Badiou ve Giorgio Agamben örneklerinin bir değerlendirmesi - Duman, Gökhan (İstanbul Bilgi Üniversitesi, 2016)
[Abstract Not Available]
Materialist theology and presocratic philosophy: an evaluatıon of the works of alain badiou and giorgio agamben